2005
DOI: 10.1016/j.ijsolstr.2005.06.016
|View full text |Cite
|
Sign up to set email alerts
|

An application of a damage constitutive model to concrete at high temperature and prediction of spalling

Abstract: A characteristic feature of concrete under uniaxial compression is the development of cracks parallel to the loading direction. A damage constitutive model proposed by Ortiz [Ortiz, M., 1985. A constitutive theory for the inelastic behaviour of concrete. Mech. Mater. 4, can predict the transverse tensile stress responsible for these cracks by considering the interaction between the aggregate and the mortar and the development of damage in the latter. When concrete is exposed to high temperature, as is the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 35 publications
1
41
0
2
Order By: Relevance
“…In the present work, both the real material strength decay (for the investigated temperatures) and the effect of the thermal stress in case of slow heating rate proved to be negligible. The effect of pore pressure seems to confirm the approach based on the effective stress assuming p s = p gas for any porosity and neglecting the role of the capillary pressure [10]. One possible interpretation is based on fracture mechanics and on the stability of the inherent material defects.…”
Section: Interpretation Of the Experimental Resultssupporting
confidence: 65%
“…In the present work, both the real material strength decay (for the investigated temperatures) and the effect of the thermal stress in case of slow heating rate proved to be negligible. The effect of pore pressure seems to confirm the approach based on the effective stress assuming p s = p gas for any porosity and neglecting the role of the capillary pressure [10]. One possible interpretation is based on fracture mechanics and on the stability of the inherent material defects.…”
Section: Interpretation Of the Experimental Resultssupporting
confidence: 65%
“…It appears during the non-stationary heating of concrete under sustained mechanical load [5,[33][34][35][36][37]. It was shown that the presence of this phenomenon could relax the compressive stresses in a column subjected to temperature [39,40] and that this strain component can reach a high magnitude. Extensive studies of this phenomenon have been conducted for ordinary concretes by [35][36][37][38].…”
Section: Transient Thermal Strain Of Concretementioning
confidence: 99%
“…Furthermore, the explosive thermal spalling of concrete during fire occurs mostly without advance notice [9,10,18,24]. It should also be noted that the presence of loading during heating influences the strength of concrete since the failure mode is generally thermal spalling when concrete is exposed to high temperature [25]. …”
mentioning
confidence: 99%